2019
DOI: 10.14254/2071-8330.2019/12-4/17
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oil price shocks on selected Kazakhstan’s macroeconomic indicators

Abstract: This article studies the correlation between world oil prices and the selected Kazakhstan's macroeconomic variables using the method of vector autoregression (VAR). As expected, the macroeconomic variables under consideration demonstrate a significant correlation with oil price fluctuations. However, the results of the research show a certain discrepancy with the earlier researches, which considered previous negative oil price shock of 2008 in the form of quicker reaction to such shocks. This means that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Economic dynamics in all three countries crucially depends on export of hydrocarbons. Following (Akhmedov, 2019;Dikkaya and Doyar, 2017;Kartaev and Medvedev, 2019) the exogenously given price of Brent crude oil brent t is chosen as a variable reflecting the dynamics of world commodity markets. The price of natural gas remains largely linked to the oil price with three to 6 months lag.…”
Section: Data and Research Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Economic dynamics in all three countries crucially depends on export of hydrocarbons. Following (Akhmedov, 2019;Dikkaya and Doyar, 2017;Kartaev and Medvedev, 2019) the exogenously given price of Brent crude oil brent t is chosen as a variable reflecting the dynamics of world commodity markets. The price of natural gas remains largely linked to the oil price with three to 6 months lag.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…Within the framework of multidimensional models, the most popular ones are vector autoregression models (VAR) and the vector error correction model (VECM), examples of which for Chile can be found in (Morandé and Schmidt-Hebbel, 2000;Schmidt-Hebbel and Werner, 2002), for Kazakhstan in (Akhmedov, 2019;Rakisheva et al, 2020;Baikulakov and Erzan, 2019), for Azerbaijan in (Hasanov and Samadova, 2010;Majidli and Guliyev, 2020). In these models two sets of variables are usually used: the first set reflects changes in the external environment as reflected in prices in world commodity markets; the second set comprised of exchange rate of the national currency against the US dollar, consumer inflation, economic growth rates, interest rate, volume of foreign exchange reserves instrumentally characterize the present economic policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also observed that structural inflation accompanies sharp declines in oil prices more than monetary inflation. Akhmedov (2019) investigated the correlation between world oil prices and selected Kazakhstan's macroeconomic variables using the VAR method. The macroeconomic variables under consideration demonstrate a significant correlation with oil price fluctuations.…”
Section: Empirical Literature For the Rest Of The Worldmentioning
confidence: 99%
“…Summing up all the above, we note that the ICO market is only an emerging market, which is not without its advantages and disadvantages, but we must not forget that everything the new needs freedom for development and self-realization, therefore, by establishing legislative barriers, it is necessary to leave the ways and opportunities for the economy to move forward [25,26,27].…”
Section: Risks In Ico and Their Managementmentioning
confidence: 99%